ANALISIS PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE TOKOPEDIA - Angga Putri Ekanova; Fransisca Riris Shinta Sari (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study was to determine the effect of brand ambassador dan brand image on purchasingdecisions at E-commerce Tokopedia. This study uses primary data. The data collection method used in thisstudy was through distributing questionnaires to 100 respondents who live in Jabodetabek. The samplingmethod in this study used non-probability sampling, with purposive sampling technique. The analyticalmethod in this study uses Validity Test, Reliability Test, Multiple Linear Regression Analysis, NormalityTest, Multicollinearity Test, Heteroscedasticity Test, t Test (partial), F Test (simultaneous), and Coefficient of Determination (R2). This study used SPSS version 28 as the testing tool. The results of this study indicatethat the brand ambassador variable can partially and significantly affect purchasing decisions at EcommerceTokopedia.The brand image variable partially and significantly can affect purchasing decisions at E-commerce Tokopedia. Simultaneously, the brand ambassador and brand image variables have a significant effect on purchasing decisions at ecommerce Tokopedia. Based on the coefficient of determination, the brand ambassador and brand image variables were quite strong in influencing purchase decisions at e-commerce Tokopedia.